The Role of Auditor Experience in Moderating the Influence of Internal Audit, Auditor Competence, and Auditor Integrity on Abuse of Authority - Poppy Damayanti; Lukas Purwoto; Faizul Mubarok (Economics and Digital Business Review, 2026)
This study aims to analyze the role of auditor experience in moderating the influence of internal audit, auditor competence, and auditor integrity on abuse of authority. This research employs a quantitative approach using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method with SmartPLS version 3.2.9. The research sample consists of 303 auditors in Indonesia, selected using a purposive sampling technique with a ratio of 10 respondents for each research indicator. The results show that internal audit has a negative and significant effect on abuse of authority, indicating that the better the implementation of internal audit, the lower the level of abuse of authority. In contrast, auditor competence and auditor integrity do not have a significant direct effect on abuse of authority, suggesting that technical ability and individual integrity alone are not sufficient to directly reduce the occurrence of abuse of authority. Furthermore, auditor experience does not moderate the effect of internal audit, auditor competence, or auditor integrity on abuse of authority. This indicates that the effectiveness of these variables is more influenced by organizational procedures, control systems, and governance mechanisms rather than individual auditor experience. These findings highlight that internal audit plays a primary role in reducing abuse of authority, while auditor competence, integrity, and experience are more effective when optimized through strong organizational systems and governance practices.